ANALISIS PENDETEKSIAN KECURANGAN PADA LAPORAN KEUANGAN - Wiwi Idawati (BAJ: Behavioral Accounting Journal, 2020)
The accounting profession is often associated with cases of financial statement fraud. The purpose of this study is to examine the effect of professional ethics, auditor experience, auditor professional skepticism on the detection of auditor fraud. The research method uses associative surveys with quantitative data and Likert scale. The research subjects used auditors from the Public Accounting Firm (KAP) in the Central Jakarta and South Jakarta areas as the population using the simple random sampling method. Unit samples were obtained by 92 respondents from 30 KAP. The analysis technique uses multiple linear regression with SPSS 22. The results of the study prove that professional ethics, auditor experience, and skepticism from auditor professionals have a large impact in detecting fraud in the preparation of financial statements. Future studies can increase the number of samples and add other independent variables that have an effect on the auditor when he sees manipulation in the financial statements.